1986
DOI: 10.1056/nejm198610303151804
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent by Proxy

Abstract: The need for clinical study of patients in nursing homes is growing as this population grows; yet many of these patients are mentally incompetent to give informed consent for such research, and the decision must therefore be left to family members or other proxies. We studied the decisions by the proxies for 168 patients in nursing homes about whether to permit the patients' participation in a study involving minimal risk. The proxies were family members in all but one case, and 78 of 168 (46 percent) refused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…It is important to study the nature and extent of these preserved abilities because they distinguish the AD research context from other situations of surrogate decision-making such as decision-making in the intensive care unit where an unconscious patient cannot provide any contemporaneous input.. Although studies have shown that surrogates’ choices do not appear to closely agree with their principal’s choices in the clinic 17 or in some research settings, 18,19 it would be a mistake to generalize those findings to the AD research context. Such studies do not simulate the situation that is common in AD research, in which patients with decisional impairments—who may retain some significant abilities such as communicating their values and preferences—remain in conversation about their decision with their surrogates.…”
Section: Two Key Ethical Conceptsmentioning
confidence: 99%
“…It is important to study the nature and extent of these preserved abilities because they distinguish the AD research context from other situations of surrogate decision-making such as decision-making in the intensive care unit where an unconscious patient cannot provide any contemporaneous input.. Although studies have shown that surrogates’ choices do not appear to closely agree with their principal’s choices in the clinic 17 or in some research settings, 18,19 it would be a mistake to generalize those findings to the AD research context. Such studies do not simulate the situation that is common in AD research, in which patients with decisional impairments—who may retain some significant abilities such as communicating their values and preferences—remain in conversation about their decision with their surrogates.…”
Section: Two Key Ethical Conceptsmentioning
confidence: 99%
“…Consequently, for each hypothetical study, the proxies' decisions for the patient were significantly more frequently in agreement with the proxies' own decisions for themselves than with the patients' decisions to participate. Similarly, 80% of proxies for nursing home residents would be willing to participate in the hypothetical study, and proxies who would take part themselves were significantly more likely to give consent for the care home resident they represented (Warren et al 1986).…”
Section: Willingness To Participatementioning
confidence: 99%
“…They reported the use of a 'best interests' approach to research decisions, even where this might override what the person's own decision might have been (Dunn et al 2012), perhaps perceiving benefits from the research that justified overriding the person's wishes in order to promote their well-being. Proxies clearly saw themselves as holding a protective role (De Vries et al 2010;Muncie et al 1997;Warren et al 1986). Some proxies did not appear to distinguish between the interests of the person and those around them:…”
Section: Best Interests Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Should substituted judgment, best interests, or some combination of both be used? Further, the question of allowing substitute consent to a research protocol for which the subject either does not or cannot give assent (register knowledgeable agreement) needs to be addressed. Some persons have advocated oversight of the proxy consent process by a disinterested fourth party or a consent auditor 10 , 12 , 33 . Prospective research needs to be conducted to determine whether such a practice would be unnecessarily cumbersome and restrictive.…”
Section: A Proposed Agenda Of Ethical Research Needsmentioning
confidence: 99%